Harnessing natural polymers and nanoparticles: Synergistic scaffold design for improved wound healing - Anitha S; Nandini Robin Nadar; Srividya Shivakumar; Sharma S C; Siddharth P; Surekha Varalakshmi V; Rajesh Lenka; Rajadurai S (Hybrid Advances)
Skin health is a vital indicator of overall well-being, notably influencing emotional and psychological states. Skin injuries which include, burns and diabetic, venous, and pressure ulcers are significant concerns in health care that are often demanding for appropriate management programs. Skin injuries may be due to acute or chronic trauma, infections, and operations and can cause severe dysfunction or death. Hence, early clinical intervention becomes crucial in managing the problem. Wound care involves many strategies from simple local dressing to complex debridement techniques such as bioactive dressings and skin grafting. Conventional wound healing products do not heal wounds adequately and can cause scarring, suggesting the possibility of new biomaterials. The current developments of applying natural polymers, which are large organic compounds obtained from renewable resources, have revealed potential utilization in biomedicine due to their inherent antibacterial and antioxidant features. These polymers are biocompatible, biodegradable, and nontoxic to the environment, therefore of great importance in developing sustainable products. The incorporation of nanoparticles brings beneficial changes to natural polymers where the antibacterial, anti-inflammatory, and mechanical property is improved. The synergistic approach results in novel scaffold designs that promote cell functions and mimic the extracellular matrix (ECM) to further enhance wound healing. The present review aims to emphasize the potential and application of natural polymers in wound treatment.